2019
DOI: 10.1080/02757206.2018.1530669
|View full text |Cite
|
Sign up to set email alerts
|

After Utopia: Leftist imaginaries and activist politics in the postsocialist world

Abstract: In this introduction to special issue 'After Utopia: Leftist Imaginaries and Activist Politics in the Postsocialist World', we explore the theoretical implications for thinking about activism as a form of historically situated practice in the former socialist world. Building on insights from the papers included in this issue, which draw on ethnographic research in Ukraine, Armenia, Bosnia and along the Balkan refugee route, our introduction considers both the fragility and resilience of leftist imaginaries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…While insightful analyses of these different kinds of activism are plentiful, surprisingly little has been written about the relationship they have to each other. Anthropological studies of activism have revealed how activists draw on historical memories and political imaginaries in order to form their identity (see Narotzky 2014;Kurtovic and Sargsyan 2019). Connecting to these insights, we content that investigating the process of activist identity formation particularly in relation to other kinds of activism is an important project for the anthropology of activism.…”
Section: Activist Identity Formations: the Question Of Ascribing Subject Positions To Marginalized Actorsmentioning
confidence: 92%
“…While insightful analyses of these different kinds of activism are plentiful, surprisingly little has been written about the relationship they have to each other. Anthropological studies of activism have revealed how activists draw on historical memories and political imaginaries in order to form their identity (see Narotzky 2014;Kurtovic and Sargsyan 2019). Connecting to these insights, we content that investigating the process of activist identity formation particularly in relation to other kinds of activism is an important project for the anthropology of activism.…”
Section: Activist Identity Formations: the Question Of Ascribing Subject Positions To Marginalized Actorsmentioning
confidence: 92%
“…The second factor accounting for the choice of new municipalism as ideological positioning is its resonance with the socialist self-management heritage. Since the 2010s, in the post-Yugoslav movement sphere there has been an attempt to revive and retrieve the historical experience of socialism (Kurtović and Sargsyan, 2019). In spite of the contested heritage of the socialist period, in the last decade the debate around ‘the unrealized potentials of Yugoslav socialism’ (Kurtović, 2019: 20) has thrived amongst intellectual circles in the area (Milan, 2021), influencing and informing the vision of the activists who created the platforms.…”
Section: Drawing From the Past: The Resonance Of Municipalist Ideas W...mentioning
confidence: 99%
“…By means of these proposals, both platforms outline a roadmap that does not require a radical institutional reform since these bodies are already in place. By ‘approaching postsocialism as an intersectional experience and geopolitically sensitive form of knowledge’ (Kurtović and Sargsyan, 2019: 2), the originators of platforms in the post-Yugoslav space rethink socialism as an emancipatory experience to draw inspiration from. This position is in line with a general revival of the socialist experience in the region’s activist scene.…”
Section: Drawing From the Past: The Resonance Of Municipalist Ideas W...mentioning
confidence: 99%
“…They objected against the political elites’ use of nationalism for their own personal gain, the corrupt privatisation processes they instigated and the growing dysfunctionality of the political systems (see Arsenijević, 2014: 47; Dragićević-Šešić and Tomka, 2016; Hromadžić and Kurtović, 2017). There was a belief that through culture and art they could enact ‘alternative futures in the aftermath of state socialist projects’ (Kurtović and Sargsyan, 2019: 3). International funders facilitated these actions.…”
Section: Why Participate? the Value Of The Creative Europe Programme ...mentioning
confidence: 99%